Transient global amnesia: neuropsychological dysfunction during attack and recovery in two "pure" cases. Issue 7 (July 1984) - Regard, M; Landis, T
Abstract : Two patients with transient global amnesia are reported. Comprehensive neuropsychological evaluation, during the amnesic episode, as well as follow-up examinations on memory were performed. The course of the amnesia was exemplified by two comparable memory tests in different modalities. Partial retrograde amnesia and complete anterograde amnesia were demonstrated during the transient episode. Objective recovery was found to be slower than subjectively experienced, but test performance was completely normal one month after onset.